2011
DOI: 10.1155/2011/721487
|View full text |Cite
|
Sign up to set email alerts
|

New Findings by High‐Order DNS for Late Flow Transition in a Boundary Layer

Abstract: This paper serves as a summary of new discoveries by DNS for late stages of flow transition in a boundary layer. The widely spread concept "vortex breakdown" is found theoretically impossible and never happened in practice. The ring-like vortex is found the only form existing inside the flow field. The ring-like vortex formation is the result of the interaction between two pairs of counterrotating primary and secondary streamwise vortices. Following the first Helmholtz vortex conservation law, the primary vort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Qualitative vortex structure comparison with experiment All these verifications and validations above show that our code is correct and our DNS results are reliable.III. Observation and Analysis by Our DNSFollowing observations have been made and reported by our previous publications(Chen et al, 2009Liu et al, 2010aLiu et al, , 2010bLiu et al, , 2010cLiu et al, , 2011aLiu et al, , 2011b Liu et al, 2011c Liu et al, , 2011dLu et al, , 2011b.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Qualitative vortex structure comparison with experiment All these verifications and validations above show that our code is correct and our DNS results are reliable.III. Observation and Analysis by Our DNSFollowing observations have been made and reported by our previous publications(Chen et al, 2009Liu et al, 2010aLiu et al, , 2010bLiu et al, , 2010cLiu et al, , 2011aLiu et al, , 2011b Liu et al, 2011c Liu et al, , 2011dLu et al, , 2011b.…”
supporting
confidence: 55%
“…In our DNS work(Chen et al, 2009Liu et al, 2010aLiu et al, , 2010bLiu et al, , 2010cLiu et al, , 2011a, 2011b 2011c, 2011d; Lu et al, 2011a, 2011b, 2011c), we have made a number of new findings on late flow transition in a boundary layer including the mechanism of large vortex structure formation, small-length scale generation and flow randomization (loss of symmetry), which can be summarized as follows (some of conclusions have been published in our previous papers):…”
mentioning
confidence: 79%
“…The classical theory, which considers "vortex breakdown" as the last stage of boundary layer transition on a flat plate, is challenged and the phenomenon of "hairpin vortex breakdown to smaller structures" is not observed by our new DNS [24,27,28]. The so-called "spikes" are actually a process of multibridge or multiring formation, which is a rather stable large vortex structure and can travel for a long distance.…”
Section: Questions To Classical Theory On Boundary Layermentioning
confidence: 94%
“…In the new DNS [27,28], it has been observed that the multiple vortex structure is a quite stable structure and never breaks down. Previously reported "vortex breakdown" is either based on 2-D visualization or made by using low pressure center as the vortex center (Figure 21(a)).…”
Section: "Vortex Breakdown Tomentioning
confidence: 94%
“…They concluded that the U-shaped vortex is a barrel-shaped head wave, secondary vortex, and is induced by second sweeps and positive spikes. In order to get deep understanding the mechanism of the late flow transition in a boundary layer and physics of turbulence, we recently conducted a high order direct numerical simulation (DNS) with 1920×128x241 gird points and about 600,000 time steps to study the mechanism of the late stages of flow transition in a boundary layer at a free stream Mach number 0.5 (Chen et al, 2009(Chen et al, , 2010a(Chen et al, , 2010b(Chen et al, , 2011a(Chen et al, , 2011bLiu et al, 2010aLiu et al, , 2010bLiu et al, , 2010cLiu et al, , 2011aLiu et al, , 2011bLiu et al, 2011cLiu et al, , 2011dLu et al, 2011aLu et al, , 2011b. The work was supported by AFOSR, UTA, TACC and NSF Teragrid.…”
Section: Nomenclaturementioning
confidence: 99%